The importance of CBCT imaging to determine the characteristics of a bone sequestrum in a case of chronic osteomyelitis - Fatih Özan; Fatma Çağlayan; İsmail Akkaş; Sinan Tozoğlu (Cumhuriyet University, 2013)
Chronic osteomyelitis may show a suppurative course with abscess or fistula formation and sequestration at some stages, and persist for a variable period up to many years with intermittent exacerbation. The importance of imaging in osteomyelitis is threefold: to localize the condition, to find out its extent, and to assess the response after treatment. Conventional multislice computed tomography is a useful method of preoperative assessment, but it is not considered as the initial choice for imaging in osteomyelitis because of its reported lack of sensitivity in bone marrow disease. The Cone Beam Computed Tomography (CBCT) is used in dentistry to image high-contrast objects such as teeth and bone and it is particularly important for several applications including treatment planning for dental implants and evaluating dental and osseous diseases in the jaws and temporomandibular joints. However, CBCT provides a lower dose, lower cost alternative to conventional CT that promises to improve the practice of oral and maxillofacial radiology. In this case report the management of a patient with persistent suppurative osteomyelitis and its treatment assisted by Cone Beam Computed Tomography (CBCT) are presented.